Aerosol Generation During Myringotomy With Tympanostomy Tube Insertion: Implications for Otolaryngology in the COVID-19 Era. (October 2021) - Campiti, Vincent J.; Ye, Michael J.; Sharma, Dhruv; Matt, Bruce H.; Mitchell, Ryan M.; Ting, Jonathan Y.; Illing, Elisa A.; Park, Jae Hong; Burgin, Sarah J.
The risk of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) transmission to health care workers during myringotomy and tympanostomy tube (MT) insertion is unknown. To determine the need for enhanced precautions to prevent potential spread via aerosolized particles, we used an optical particle sizer to measure aerosol generation intraoperatively during a case series of MT insertion. We also discuss our institutional experience with safe pandemic-era perioperative practices. There was no measured increase in aerosol particle number during the procedure at a distance of 30 cm from the external auditory canal. These initial data are reassuring regarding the risk of SARS-CoV-2 transmission to the operating room team due to aerosol generation, but further study is necessary before making definitive recommendations.